Burnout Levels In Covid-19 Patients Undergoing Self Isolation In The Work Area Of Puskesmas Bangkala, Makassar - Rosnania; Afrida; Kurniawan Amin (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2022)
Patients who are positive for Covid-19 will be isolated for 10 days in the hospital or isolated independently at home if their condition is fine and without severe symptoms. Isolated for 10 days can make patients feel bored because of restricted access. Stress can be caused by many factors such as excessive worry about physical conditions, feelings of anxiety because they can't get together with family or feeling bored because of the treatment being undertaken. This study is a descriptive study with a survey method to describe the level of burnout in Covid-19 patients undergoing self-isolation in the work area of ​​the Puskesmas Bangkala. In this study, data were collected from 30 respondents using a questionnaire. The results showed that the burnout level for Covid-19 patients who underwent self-isolation in the work area of ​​the Puskesmas Bangkala mostly experienced a medium burnout level of 50%. For covid-19 patients so as not to experience burnout while undergoing self-isolation, it is better to do fun things for yourself, pray a lot to calm the mind, filter out true news about the covid-19 disease, continue to comply with health protocols, maintain good air circulation. both in isolation, exercise regularly, and always check the temperature and oxygen saturation.